Ideology, Power, and Policy: A Discourse Analysis of the Merdeka Belajar Curriculum in Higher Education - Nur Shabrina Atsarina Ramadhani; Elina Nurrohmah; Khuzaimah; Imma Latifa; Moh. Mudzakkir; Putri Dwi Permata Indah (Soshum: Jurnal Sosial dan Humaniora, 2025)
As the highest authority in Indonesia’s education sector, Nadiem Makarim plays a crucial role in shaping the discourse on ideal education through curriculum policies. However, the implementation of the Merdeka Belajar (Independence Policy) in higher education has sparked both support and criticism. This study aims to analyze the discourse surrounding the policy’s implementation using a qualitative approach and Sara Mills’ discourse analysis framework, which examines actor positioning within texts. Research data is sourced from media texts, and the study applies Michael W. Apple’s theory of ideology and power, which argues that educational institutions not only regulate behaviour but also shape the meaning of knowledge within the curriculum. Findings reveal two key aspects of Sara Mills’ discourse analysis: position-object analysis and author-reader positioning. The study identifies the Indonesian government, represented by the Ministry of Education, Culture, Research, and Technology (Kemdikbudristek), as the dominant actor with authority over decision-making. Meanwhile, students, educators, and education practitioners serve as both implementers and beneficiaries of the policy. The research highlights how Kemdikbudristek, as a power holder, influences the discourse on ideal higher education through the Merdeka Belajar curriculum, which is shaped by various ideological factors, including the perspectives of its leadership. This study contributes to discussions on curriculum formulation in higher education and offers insights for policymakers in designing future education policies.